Electrospun PEDOT:PSS/PVP Nanofibers for CO Gas Sensing with Quartz Crystal Microbalance Technique - Hong-Di Zhang; Xu Yan; Zhi-Hua Zhang; Gu-Feng Yu; Wen-Peng Han; Jun-Cheng Zhang; Yun-Ze Long (International Journal of Polymer Science)
Poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)/polyvinylpyrrolidone (PEDOT:PSS/PVP) composite nanofibers were successfully fabricated via electrospinning and used as a quartz crystal microbalance (QCM) sensor for detecting CO gas. The electrical property of individual PEDOT:PSS/PVP nanofibers was characterized and the room temperature resistivity was at the magnitude of 105 Ω·m. The QCM sensor based on PEDOT:PSS/PVP nanofibers was sensitive to low concentration (5–50 ppm) CO. In the range of 5–50 ppm CO, the relationship between the response of PEDOT:PSS nanofibers and the CO concentration was linear. Nevertheless, when the concentration exceeded 50 ppm, the adsorption of the nanofiber membrane for CO gas reached saturation and the resonant frequency range had no change. Therefore, the results open an approach to create electrospun PEDOT:PSS/PVP for gas sensing applications.